Foundations of software testing - Mathur, Aditya P (New Delhi : Pearson, 2013)
Foundations of Software Testing, Second Edition is aimed at the undergraduate, the graduate student, and the practicing engineer. It presents sound engineering approaches for test generation, ion, minimization, assessment, and enhancement. Using numerous examples, it offers a lucid description of a wide range of simple to complex techniques for a variety of testing-related tasks. It also discusses the comparative analyses of commercially available testing tools to facilitate the tool ion.
Index 673-697p.
Keywords: Integration testing; Test selection; Predicate analysis